The role of business in addressing the long-term implications of the current food crisis - Yach Derek (BMC, 2008)
Abstract Before the onset of the current food crisis, the evidence of a severely neglected nutrition crisis was starting to receive attention. Increased food prices are having severe impacts on the nutritional status of populations. Our current food system has evolved over decades in a largely unplanned manner and without consideration for the complexity and implications of linkages between health, nutrition, agricultural, economic, trade and security issues. The underlying causes for the nutrition crisis include the above, as well as decades of neglect with regard to nutrition, and agricultural science (especially in emerging markets); a failure of governance with respect to the major players involved in nutrition, a weak response by government donors and Foundations to invest in basic nutrition (in contrast to growing support for humanitarian aspects of food aid), and a reluctance to develop private-public partnerships. The emergence of new business models that tackle social problems while remaining profitable offers promise that the long term nutrition needs of people can be met. Businesses can have greater impact acting collectively than individually. Food, retail, food service, chemical and pharmaceutical companies have expertise, distribution systems and customers insights, if well harnessed, could leapfrog progress in addressing the food and nutrition crises. While business can do lots more, its combined impact will be minimal if a range of essential government actions and policies are not addressed. Governments need to create innovative and complementary opportunities that include incentives for businesses including: setting clear nutritional guidelines for fortification and for ready-to eat products; offering agreements to endorse approved products and support their distribution to clinics and schools; eliminating duties on imported vitamins and other micronutrients; and providing tax and other incentives for industry to invest with donors in essential nutrition and agricultural research. Currently governments in developed countries provide a wide range of incentives to the pharmaceutical industry to develop medicated solutions to nutritional problems. We need equivalent effort to be given to the development of more sustainable agricultural and food based solutions. We now face a truly global set of interlinked crises related to food that affect all people. The same degree of urgency and high level leadership and partnership seen during the Second World War is required on a global basis. This time it will need to simultaneously address agricultural, environmental and health considerations with the aim being the attainment of optimal nutrition for all within a framework of sustainable development.